Presence and participation in a virtual court - Rossner, Meredith (Criminology & criminal justice, 2023)
The COVID-19 pandemic has led to an increase in the use of video-mediated justice practices. However, such developments have already been transforming justice over the course of the previous 20 years. Scholars and legal professinals have expressed concerns over how remote appearance in court impacts perceptions of the accused. In this article, we consider some of these concerns and explore the concept of the ‘distributed court’ as a potential remedy. Unlike traditional video appearance in court, where a defendant participates remotely while all other players are co-located in the same courtroom, in a distributed court all participants meet in a shared virtual space. Such a configuration is similar to the virtual courts developed worldwide during the COVID-19 pandemic. We draw on a reimagining of co-presence from scholars in the sociology of technology to elaborate the concept of the distributed court. We then present the results of a mock jury study that examines how jurors respond to variations in court technology configurations. We find that appearing by video does not impact the likelihood of a guilty verdict. Rather, a defendant appearing alone in a dock seems to be the most prejudicial location. We find that a distributed court can communicate equality and produce a shared experience of remote participation. We conclude with a discussion of how this research can inform best practice in a future where a significant number of criminal hearings are likely to continue in a virtual format.